Tradisi Barong Ider Bumi di Desa Kemiren, Banyuwangi: Dari Ritual Sakral ke Festival Kultural - Isnaini, Iin; Bella Riskika Taufik (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Barong Ider Bumi is a unique tradition found in Kemiren Village, Banyuwangi, which functions as a village cleaning ritual as well as a means of warding off bad luck. This tradition involves Barong as a mediator between humans and the ancestral spirit, Buyut Cili, who is believed to be the protector of the village (dhanyang). The main purpose of this ritual is to express gratitude and ask for protection from various epidemics, with the hope that the people of Kemiren Village will live safely and peacefully. This research focuses on two aspects, namely: (1) the historicity of Barong Ider Bumi in Banyuwangi Regency, and (2) the changes of this tradition in the period 2000-2012. The research uses the historical method, which includes the stages of topic selection, heuristics, source criticism, interpretation, and historiography. The results show that the Barong Ider Bumi tradition has been going on since the past, starting as a response to a disease outbreak (pagebluk) that attacked Kemiren Village. Since then, the tradition has evolved, especially after it became part of the Banyuwangi Festival (B-Fest) organized by the local government. The inclusion of this tradition in B-Fest broadens participation, by involving various local arts in the procession of the Barong procession.